European trade and foreign direct investment U-Shaping industrial output in Central and Eastern Europe: Theory and evidence - Alexander Repkine; Patrick Paul Walsh (Katholieke Universiteit Leuven, LICOS Centre for Transition Economics, 1998)
We examine the evolution of industrial output in Bulgaria, Hungary, Poland and Romania over the period 1989-1995 in terms of product trade orientation prior to the transition process, some products traded in a market economy while others traded in the artificial market of the Soviet Bloc. We theoretically and empirically model the growth dynamics of EU oriented output within sectors of industry, ex-post trade and market liberalisation, as Foreign Direct Investment (FDI) induced Schumpeterian (vertical) waves of product innovation. We estimate the growth dynamics of non-EU oriented output within sectors as unobservable deterministic sector and country specific heterogeneity. The results indicate that the evolution of industrial production within sectors that were EU oriented prior to transition grew with increasing convexity over time. This growth was unconstrained by the transition process due to increased access to the European market, foreign capital and foreign expertise. Pre-transition non-EU industrial production is estimated to follow the same pattern as that observed in CIS countries. Hence the faster recovery, or the U-Shape industrial output, observed in CEE as compared with CIS countries is mainly explained by the inherited presence of EU oriented production and its unconstrained growth over the transition period.
Keywords: F43; O33; P23; 330; Foreign Direct Investment; Industrial Output Growth; Transition Economies; Cross-Country and Branches of Industry Regressions